Pharmacological activity of OST-01, a natural product from baccharis coridifolia, on breast cancer cells - HyunJun Kang; Dinh Hoa Hoang; Melissa Valerio; Khyatiben Pathak; William Graff; Alexis LeVee; Jun Wu; Mark A. LaBarge; David Frankhouser; Russell C. Rockne; Patrick Pirrotte; Bin Zhang; et al. (Journal of Hematology & Oncology)
Abstract Natural products have long been a viable source of therapeutic agents, providing unique structures and mechanisms that may be beneficial for cancer treatment. Herein we first report on the anticancer activity OST-01, a natural product from Baccharis Coridifolia, on breast cancer cells, including triple-negative breast cancer (TNBC). OST-01 significantly inhibited cell proliferation and oncogenic activities of TNBC cells in vitro. OST-01 also markedly inhibited TNBC tumor growth in vivo, with > 50% reduction in tumor size compared to vehicle control treatment in different in vivo models, i.e., cell line-derived (CDX), patient-derived (PDX), and mammary fat pad xenografts. Mechanistically, OST-01 induces ferroptosis by downregulating LRP8-regulated selenoproteins, i.e., GPX4. A shift from a basal-mesenchymal to a luminal-epithelial state of breast cancer stem cells (BCSCs) as supported by the downregulation of stemness (e.g., CD44) and mesenchymal (e.g., FN1 and vimentin) markers, along with the upregulation of differentiation markers (e.g., CD24) and luminal-epithelial markers (e.g., CK19), was also observed.